Lessons from a Quechua strongwoman : ideophony, dialogue, and perspective - Nuckolls, Janis B. (First peoples (2010), 2010)
"Nuckolls shows through detailed data analysis how much the scholarly community still has left to learn. The materials are very rich, and the narratives themselves, effectively translated by the author, energe as works of art in their own right"--Michael Uzendoski, author of The Napo Runa of Amazonian Ecuador.